Use of Rosetta Stone Application as Online Learning Media in Learning German for Tenth-Graders of Language Studies Major at SMA Laboratorium UM - Cessy Nooraeni Rimeldi; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The research aims to depict students' activities using Rosetta Stone as the online learning media in learning German at SMA Laboratorium UM. The study was also looking for students' responses towards the use of the application. The research design used in this research was descriptive qualitative. The participants of the research consist of 22 students of tenth-graders majoring in language studies. The researcher obtained the data from observation and interviews. The researcher did the investigation to learn the activity of using the application in online learning German. The researcher interviewed the students to get responses from the students using the application as their online learning media. The result revealed that the application gave new exciting experiences in learning language, mainly German. The research had shown that the students actively engaged and gave a positive attitude towards the learning and teaching process, with the result that fostering learning independence. Students were able to access the materials in the application, and they understood the materials given comprehensively. Following the learning activity, the goal of the research was well achieved.